Oct 2014 - PAME Progress Report to SAOs. - Protection of the Arctic Marine Environment (PAME) (Protection of the Arctic Marine Environment (PAME), 2014)
Progress report from the Arctic Council working group Protection of the Arctic Marine Environment (PAME). Submitted to the Arctic Council's Senior Arctic Officials meeting in Yellowknife, Canada, October 22-23 2014.